TINJAUAN ATAS PENERIMAAN PAJAK PENGHASILAN PASAL 23 DI KANTOR PELAYANAN PAJAK PRATAMA MUARA TEWEH TAHUN 2017-2019 - Darozatun Nur Fadillah; Yohana Yustika Sari; Ayu Oktaviani (Universitas Lambung Mangkurat, 2021)
The preparation of this Final Project is carried out to deepen the understanding of how the Income Tax Article 23 at the Muara Teweh Tax Office is maximized as a source of revenue. The research was conducted at the Muara Teweh KPP using data on revenue targets and realization for 2017-2019. In general, Income Tax Article 23 at the Muara Teweh Tax Office has a Target and Realization Growth Report every year. However, each year has a different target and realization, so it is necessary to elaborate and make comparisons by calculating each year, it will be seen that there will be a decrease and increase in Article 23 Income Tax revenue that occurs at the KPP Pratama Muara Teweh so efforts must be made to increase revenue. income tax